KEHIDUPAN SOSIAL EKONOMI MASYARAKAT DESA KERSIK TUO SEBAGAI DESA PENYANGGA PARIWISATA GUNUNG KERINCI (2013-2018) - Febri Yonata; Z Zulfa; Livia Ersi (Horizon, 2021)
This research generally discuss about social and economic conditions in Kersik Tuos Village as a Tourism Destination, were Kerinci mountain become favorites choice for montain climber, which one this icons located in Kerinci Seblat National Park area with an altitude of 3805 Masl. Kersik Tuo Village has long been a center of mobility as well as a transit point for tourists, and also the people also provides various kinds of needed for tourists. There are many of social and economic relations that exist in the community, for this reason the people of Kersik Tuo Village do not really see a tourism as a field to advance the community's economy. The purpose of this research is to explain the socio-economic conditions of the Mount Kerinci tourism support community in Kersik Tuo in 2013-2018 and to explain the people's role of Kersik Tuo in Supporting Mount Kerinci Tourism. The research method that used in this research is historical research, that combines Heuristik, critically resources, Interpretation and historiography. The result of this research, Kersik Tuo Village is a village that nearest from Kerinci mountain. The population in Kersik Tuo mostly in agriculture and trade. The tourism have an effect for Social¬ - Economic conditions of the Tersik Tuo society as a support for Mount Kerinci Tourism and always advancement from 2013 until 2018. This is added with people that participating in sector, like a service industry, trademark, etc. The people realize that the tourism is important to developed Kersik Tuo village.